Konseling Kelompok Dengan Pendekatan Humanistik Untuk Menangani Kecemasan Karena Pelanggaran Privasi Di Dalam Keluarga - rizka, hikmah amalia; Izzatti, Aliffiyah; Abdi, Sofyan; Hasna, Afra; Fitria, Zahra; Rahman, Tazqiyatur; Anggraini, Ririn (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The family as the smallest social unit has an important role in the formation of personality and emotional well-being of individuals. However, violations of privacy in family relationships can cause psychological tension and feelings of anxiety, especially in adolescents and students. This study aims to understand the experiences of students who experience violations of privacy in the family environment and to describe the dynamics of group counseling with a humanistic approach in helping to manage the anxiety experienced. The research approach used was qualitative with a case study design, involving six students who participated in group counseling services. The findings showed that group counseling provided a safe and supportive space for participants to express their feelings and obtain emotional support. This resulted in increased self-awareness, emotional relief, and decreased levels of anxiety felt. This study contributes to the development of counseling practices, especially in the application of a humanistic approach to assist individuals experiencing emotional crises in the family context.